Weight bias internalization, core self‐evaluation, and health in overweight and obese persons. (10th September 2013) - Hilbert, Anja; Braehler, Elmar; Haeuser, Winfried; Zenger, Markus
<x xml:space="preserve">Abstract</x> Objective Weight bias has strong associations with psychopathology in overweight and obese individuals. However, self‐evaluative processes, as conceptualized in the process model of self‐stigma, and implications for other health‐related outcomes, remain to be clarified. Design and Methods In a representative general population sample of N = 1158 overweight and obese individuals, the impact of core self‐evaluation as a mediator between weight bias internalization and mental and global health outcomes as well as between weight bias internalization and health care utilization, was examined using structural equation modeling. Results In overweight and obese individuals, greater weight bias internalization predicted lower core self‐evaluation, which in turn predicted greater depression and anxiety, lower global health, and greater health care utilization. These mediational associations were largely stable in subsample analyses and after controlling for sociodemographic variables. Conclusions The results show that overweight and obese individuals with internalized weight bias are at risk for impaired health, especially if they experience low core self‐evaluation, making them a group with which to target for interventions to reduce self‐stigma. Weight bias internalization did not represent a barrier to health care utilization, but predicted greater health care utilization in association with greater health impairments.